Role of ex vivo Expanded Mesenchymal Stromal Cells in Determining Hematopoietic Stem Cell Transplantation Outcome - Crippa, Stefania; Santi, Ludovica; Berti, Margherita; De Ponti, Giada; Bernardo, Maria Ester (Frontiers in Cell and Developmental Biology, 2021)
Overall, the human organism requires the production of ~one trillion new blood cells per day. Such goal is achieved via hematopoiesis occurring within the bone marrow (BM) under the tight regulation of hematopoietic stem and progenitor cell (HSPC) homeostasis made by the BM microenvironment. The BM niche is defined by the close interactions of HSPCs and non -hematopoietic cells of different origin, which control the maintenance of HSPCs and orchestrate hematopoiesis in response to the body requirements. The activity of the BM niche is regulated by specific signaling pathways in physiological conditions and in case of stress, including the one induced by the HSPC transplantation (HSCT) procedures. HSCT is the curative option for several hematological and non-hematological diseases, despite being associated with early and late complications, mainly due to a low level of HSPC engraftment, impaired hematopoietic recovery, immune mediated graft rejection, and Graft-versus-Host-Disease (GvHD) in case of allogenic transplant. Mesenchymal stromal cells (MSCs) are key elements of the BM niche, regulating HSPC homeostasis by direct contact and secreting several paracrine factors. In this review we will explore the several mechanisms through which MSCs impact on the supportive activity of the BM niche and regulate HSPC homeostasis. We will further discuss how the growing understanding of such mechanisms have impacted, under a clinical point of view, on the transplantation field. In more recent years, these results have been necessary to ameliorate the outcome of HSCT, especially in the context of allogenic transplants, and when low doses of HSPCs were available for transplantation.